PROSPECT OF CO-MANAGEMENT APPROACH IN MANAGING FISHERIES IN INDONESIA: Closer Look on Ikan Larangan (“Forbidden fish farming”) System in West Sumatra - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Ikan Larangan is a good example of the revived traditional community-based resource management in Indonesia. Purposive sampling was employed to withdraw 99 household samples in the study area. A research framework for institutional analysis as recommended by ICLARM (Pomeroy, 1993) was applied to this study. The results found that the average score of the 11 key-conditions for successful Co-management is close to 4. This indicates that the prospects for Co-management application of Ikan Larangan system is sound. Therefore, the salient approach of Co-management could be adopted to prescribe acceptable fisheries resource management in Indonesia.